Does Size Grading Improve Fish Farming? Evidence From a Meta‐Analysis - Chenchen Wu; Ze Zhu; Yanci Wen; Songming Zhu; Ying Liu; Kai Liu; Yi‐Jia Shih; Zhangying Ye; Xingguo Liu; Jian Zhao (Reviews in Aquaculture, 2026)
Size grading, sorting a cohort into more homogeneous size classes, is widely used in aquaculture and presumed to enhance production efficiency. However, reported effects on fish growth are inconsistent. To address this uncertainty, we conducted a comprehensive meta‐analysis spanning 32 species to systematically evaluate the effect of size grading on fish growth and to identify key moderators of this effect. Overall, size grading reduced the average specific growth rate (SGR) by 4.50%. Species personality type (aggressive vs. docile) was the most important among the moderators tested: grading significantly reduced average SGR in docile species but had no effect in aggressive ones; and in both aggressive and docile species, the effect of grading depended positively on the initial variation coefficient (IVC). We emphasized that aggressive behaviour is closely associated with the effects above and pointed out the role of IVC between frequency of aggressive behaviour (FAB) and daily food intake (DFI) in aggressive species. We also found size grading had opposing effects on changes in size heterogeneity, which is beneficial for aggressive but not docile species. Besides, while size grading significantly reduced cannibalism rate (CR) in both personality types, it was at the cost of overall SGR. Therefore, size grading may not be advisable for docile species due to growth suppression. For aggressive species, size grading generally reduces overall production, but it is recommended from an individual quality standpoint, provided a moderate size heterogeneity is maintained.

Disinfection By‐Products in Aquaculture: Sources, Impacts, Removal and Future Research - Ze Zhu; Amit Gross; Paul B. Brown; Guozhi Luo (Reviews in Aquaculture, 2025)
Aquaculture disinfection processes are critical for biosecurity, especially with the rapid development of intensive aquaculture, yet they also yield disinfection by‐products (DBPs) with significant and underexplored impacts on aquatic organisms and humans. This review provides the first comprehensive evaluation of DBPs in aquaculture, focusing on their sources, environmental and health impacts, removal strategies, and future research directions. It provides a deep analysis of DBP sources, including disinfectants, organic precursors, additives like antibiotics and hormones, and their transformation pathways in aquaculture environments. The review further assesses the ecological and physiological effects of DBPs on aquatic species, along with the human health risks posed by DBP bioaccumulation. Current DBP removal strategies are evaluated, highlighting technological gaps and advocating for advanced, aquaculture‐specific solutions, such as enhanced filtration, biofiltration, and low‐DBP disinfection methods. Despite evidence of their harmful effects on fish health, ecosystem stability, and potential human exposure, DBPs in aquaculture lack adequate risk assessments and regulatory frameworks. This review underscores the urgent need for robust monitoring systems, targeted toxicity research, and a cohesive regulatory structure to manage DBPs, thereby advancing sustainable aquaculture practices that safeguard environmental and public health.

Water Quality Impact on Fish Behavior: A Review From an Aquaculture Perspective - Kaisheng Zhang; Zhangying Ye; Ming Qi; Wenlong Cai; João L. Saraiva; Yanci Wen; Gang Liu; Ze Zhu; Songming Zhu; Jian Zhao (Reviews in Aquaculture, 2025)
Changes in water quality significantly shape fish behavior, a crucial index reflecting the growth and welfare status of fish. Given the centrality of this relationship to aquaculture practices, a comprehensive understanding of how water quality dynamics influence fish behavior is imperative. While there have been some summaries of the effects of water quality parameters on fish physiology and growth, few reviews on their effects on fish behavior have been reported yet. This article reviews several water quality parameters which are of great concern in aquaculture from multiple facets of actual production, including physical parameters (water temperature and turbidity), chemical parameters (dissolved oxygen, salinity, pH, and inorganic nitrogen), and chemical pollutants (microplastics and crude oil), which have gained increasing attention from the researchers and aquaculture practitioners over the past decades. Variations in these water quality parameters can exert profound effects on fish physiology, metabolism, internal tissues and organs, and sensory perception, which influences fish behaviors such as swimming, schooling, feeding, predation, anti‐predation, aggression, courtship, as well as adaptive and stress‐related behaviors such as exploration, avoidance response, and anxiety‐like behavior. By synthesizing the behavioral changes caused by specific water quality parameters, this review aims to provide strong support for further water quality‐related research, thereby fostering environments conducive to both fish welfare and aquaculture productivity.